Cooperation mechanisms in Singapore-China relations : a case study of the joint council for bilateral cooperation - Goh, Venus Qianyi (2017)
Singapore-China relations is widely regarded as a broad-based relationship rooted in cooperation. This paper looks into these institutionalised cooperation mechanisms to evaluate its role in bilateral relations. In analysing the case studies of the Joint Council for Bilateral Cooperation and the three government-to-government flagship projects, this paper found the importance of cooperation mechanisms to be understated in existing literature. Based on interviews conducted with relevant experts and academics, this paper established that the purpose of cooperation mechanisms is not limited to that of a platform for engaging on cooperation projects. More importantly, it plays a crucial role in serving as an impetus for conflict resolution, and in cultivating personal ties between the leaders and ministers of both countries. This paper concludes that cooperation mechanisms will continue to play a crucial role in fostering good relations between Singapore and China.